Analysis of Annual Total Revenues of the Iraqi National Insurance Company - Ghadhanfer A. Hussein; Ameen Al Htibat (Journal of Techniques)
Among the most significant non-banking financial institutions, insurance businesses must endeavor to sustain their insurance activities by generating a variety of revenues that allow them to operate their company actively and continually. This is necessary to secure their development and reliability. The current study intends to analyse the annual total data of different types revenues of Iraqi National Insurance company besides investigating the elements that influence the insurance income during 2010–2015. This study advances knowledge about the insurance sector, offers insights for academics, investors, and regulators, and has practical consequences for the operating plans of the Iraqi National Insurance Company. It supports the objectives of enhancing financial performance, controlling risks, and developing a competitive and long-lasting insurance market. The current study attempts to validate hypotheses indicating that rising insurance premium costs, growing insurance operations, greater investment in activities, and higher-valued additional revenues all contribute to the National Insurance Company's overall revenue growth. The most notable finding of this research is that insurance premiums collected by the insurance company are the most significant factor in the level of revenues during the study period. The Iraqi National Insurance Company is advised to diversify its revenue streams in order to achieve high rates of return and enhance its capacity to grow.